Idiostylistic Parameters of Fictional Discourse - Kononenko, Vitaliy (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article discusses issues associated with identifying the authorial style of modern Ukrainian writers with an emphasis on trends in the development of a renewed writing manner. The author analyzes changes in fictional discourse in general and in the idiostyle of particular authors, which allows for the possibility of identifying patterns in the modernization of stylistic devices, the renewal of imagery, the development of novostyl